ChemInform Abstract: ZnO Nanoparticles: An Efficient Green Reusable Catalyst for the Synthesis of 3‐Formyl Benzopyranones Chalcones by Claisen—Schmidt Reaction under Solvent‐Free Condition. Issue 15 (24th March 2016) - Chand, Subhash; Sandhu, Jagir S.
Abstract: The protocol is simple, rapid, and environmentally benign.